2014
DOI: 10.3892/ol.2014.2091
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lung tumor growth in nude mice by siRNACD31 targeting PECAM-1

Abstract: Small interfering RNA (siRNA) provides a promising therapeutic approach in the silencing of disease-causing genes. In the present study, the use of 2′-O-methyl-modified siRNA-cluster of differentiation 31 (siRNACD31), with cationic liposome RNA interference (RNAi)-mate as a carrier, effectively silenced the platelet endothelial cell molecule 1 (PECAM-1) gene of murine hemangioendothelioma cells in vitro. In vivo, 2′-O-methyl-modified siRNACD31 carried by RNAi-mate was successfully delivered, targeting the PECA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
3
4
0
Order By: Relevance
“…Collectively, these results suggested that PECAM -1 might be an attractive target for cancer therapy and an important regulator in determining drug resistance of tumor cells after ionizing irradiation. This notion was also supported by recent studies showing that the growth of mantle cell lymphoma in a xenograft model was associated with upregulated PECAM-1 expression (27) and that PECAM-1 siRNA inhibited tumor growth in a lung carcinoma xenograft model (28) . It was assumed that reduced PECAM-1 expression might attenuate the activities of several pro-survival pathways involving PECAM-1 signaling complexes, such as Bcl-2 family proteins, PI3K/ Akt, pathway, and NF-kB activity.…”
supporting
confidence: 60%
“…Collectively, these results suggested that PECAM -1 might be an attractive target for cancer therapy and an important regulator in determining drug resistance of tumor cells after ionizing irradiation. This notion was also supported by recent studies showing that the growth of mantle cell lymphoma in a xenograft model was associated with upregulated PECAM-1 expression (27) and that PECAM-1 siRNA inhibited tumor growth in a lung carcinoma xenograft model (28) . It was assumed that reduced PECAM-1 expression might attenuate the activities of several pro-survival pathways involving PECAM-1 signaling complexes, such as Bcl-2 family proteins, PI3K/ Akt, pathway, and NF-kB activity.…”
supporting
confidence: 60%
“…PECAM-1 is a diagnostic membrane protein used to demonstrate the presence of endothelial cells in histological tissues [ 40 , 42 ]. It is also expressed in certain tumours, which can imply a rapidly growing tumour because of its involvement in angiogenesis, for this reason PECAM-1 has been used as an angiogenic target in cancer therapies [ 5 , 25 ]. Previous in vitro studies in human and animal cell cultures showed that PECAM-1 expression increased when endothelial cells were exposed to irradiation doses from 10 to 20 Gy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…These agomirs were then dissolved into RNasefree water to obtain a working solution of 20 mM. We mixed 10 mL of each agomir or siRNA with 10 mL of siRNA-MateTM transfection reagent (GenePharma, Shanghai) and 80 mL of PBS to serve as the transfection solution [25,26]. Twenty sea cucumbers (60 ± 10 g)…”
Section: Mir-31 Over-expression and Target Gene Silencing By Sirna Inmentioning
confidence: 99%